Bank Portfolio Selection - Fried, Joel (Journal of Financial and Quantitative Analysis, 1970)
This paper describes the development and testing of a model of bank portfolio selection that considers variability of both income and gross asset levels as the risks involved in banking. In particular, the model is formulated as maximizing expected profit subject to risk constraints on wealth losses and the availability of liquid assets. The parameters for these constraints include the covariance matrices of rates of return on bank assets and deposit changes. Included in the latter category are fluctuations in business loans which are treated as negative deposits because, due to deposit feedbacks and the like, these can reasonably be considered exogenous to the short-run portfolio decision. Basically, the model is an extension of Markowitz's work [11] to incorporate problems associated with portfolios that include assets having imperfect markets and liabilities that are not completely under the control of the economic unit. As such, it is applicable (with minor institutional modifications) to the entire spectrum of financial intermediaries.